REVIEW ARTICLE BENEFIT OF VOLATILE ORGANIC COMPOUNDS IN CITRUS SPECIES - Nerdy Nerdy; Nilsya Febrika Zebua; Syarifah Nadia; Kharina Tambunan; Fatia Zahra; Tedy Kurniawan Bakri (FORTE JOURNAL, 2025)
The volatile organic compounds in Citrus species, such as oranges, limes, and lemons, are crucial for both plant ecology and various human applications. This review article explores the diverse benefits of Citrus volatile organic compounds, highlighting their roles in plant defense mechanisms, pollinator attraction, and intraspecies communication. The chemical composition of Citrus volatile organic compounds includes key compounds like limonene, β-linalool, trans-citral, β-myrcene, α-Pinene, β-Pinene, γ-Terpinene, and Terpineol, which exhibit significant anti-microbial, anti-inflammatory, anti-oxidant, and potential anti-cancer properties. These compounds are integral to human health, utilized in aromatherapy, and enhancing mood and reducing anxiety. Industrially, Citrus volatile organic compounds are indispensable in the food and beverage industry as flavoring agents, in cosmetics and personal care products for their refreshing scents and skin benefits, and in cleaning products for their anti-microbial properties. Furthermore, their therapeutic potential has led to their inclusion in pharmaceutical and nutraceutical products. This review underscores the multifaceted role and economic significance of Citrus volatile organic compounds, advocating for continued research and technological advances to fully harness their benefits in health, industry, and sustainability.